Investigation on the Stoichiometry of Carbon Dioxide in Isotope-Exchange Reactions with Phenylacetic Acids - Talbot, Alex; Sallustrau, Antoine; Goudet, Amélie; Taran, Frédéric; Audisio, Davide (Synlett, 2021)
The functionalization of carbon dioxide (CO2) as a C1 building block has attracted enormous attention. Carboxylation reactions, in particular, are of major interest for applications in isotope labeling. Due to the inexpensive nature of CO2, information about its stoichiometric use is generally unavailable in the literature. Because of the rarity and limited availability of CO2 isotopomers, this parameter is of concern for applications in carbon-isotope labeling. We investigated the effects of the stoichiometry of labeled CO2 on carbon isotope exchange of phenylacetic acids. Both thermal and photocatalytic procedures were studied, providing insight into product outcome and isotope incorporation. Preliminary results on isotope-dilution effects of carbonate bases in photocatalytic carboxylation reactions have also been obtained.
Keywords: carbon dioxide; isotope labeling; photoredox catalysis; decarboxylation; carboxylation